Cereal β-d-Glucans in Food Processing Applications and Nanotechnology Research - Lucie Jurkaninová; Václav Dvořáček; Veronika Gregusová; Michaela Havrlentová (Foods, 2024)
Cereal (1,3)(1,4)-β-d-glucans, known as β-d-glucans, are cell wall polysaccharides observed in selected plants of grasses, and oats and barley are their good natural sources. Thanks to their physicochemical properties β-d-glucans have therapeutic and nutritional potential and a specific place for their functional characteristics in diverse food formulations. They can function as thickeners, stabilizers, emulsifiers, and textural and gelation agents in beverages, bakery, meat, and extruded products. The objective of this review is to describe the primary procedures for the production of β-d-glucans from cereal grains, to define the processing factors influencing their properties, and to summarize their current use in the production of novel cereal-based foods. Additionally, the study delves into the utilization of β-d-glucans in the rapidly evolving field of nanotechnology, exploring potential applications within this technological realm.